Sintesa Hukum Islam dan Kebudayaan Jawa Suatu Pendekatan Profetik /The Synthesis of Islamic Law and Javanese Culture A Prophetic Approach - Suwandi, Suwandi; Setyobudi, Teguh (De Jure: Jurnal Hukum dan Syari'ah, 2020)
Abstract: Islamic law and culture are still interesting themes. The two of them often sit in confrontation and opposition. Meanwhile, in practice the implementation of Islamic law cannot be separated from the culture of the local community. In the context of Javanese society, for example, Islamic law has synergized with adat in the context of forming a noble and civilized character of society. This article aims to analyze the relationship between Islamic law and Javanese culture. The two are often positioned contradictory. This article is the result of doctrinal legal research using a sociological approach. The results of this study indicate that the relationship between Islamic law and Javanese culture is compromise. Both of them establish a partnership relationship with roles and functions proportionally. The values of humanization, liberalization, and transcendence are meeting points between Islamic law and Javanese culture. The sacred text needs to be objectified and contextualized in the context of the development process of a religious Javanese society.Keywords: Islamic law; Javanese culture; prophetic.Â Abstrak: Hokum Islam dan budaya masih menjadi tema menarik. Keduanya tidak jarang diduduknya secara konfrontatif dan berseberangan. Sementara itu, dalam praktiknya implementasi hokum Islam tidak dapat dipisahkan dari budaya masyarakat setempat. Dalam konteks masyarakat Jawa misalnya, hukum Islam telah bersinergi dengan adat dalam rangka pembentukan karakter masyarakat yang luhur dan beradab. Artikel ini bertujuan menganalisis relasi hukum Islam dan kebudayaan Jawa. Keduanya sering diposisikan secara kontradiktif. Artikel ini merupakan hasil penelitian hukum doktrinal dengan pendekatan sosiologis. Hasil penelitian ini menunjukkan bahwa relasi hukum Islam dan budaya Jawa bersifat kompromistik. Keduanya menjalin hubungan kemitraan dengan peran dan fungsi secara proporsional. Nilai humanisasi, liberalisasi, dan transendensi merupakan titik temu antara hukum Islam dan kebudayaan Jawa Teks suci perlu dilakukan Obyektifikasi dan kontekstualisasi dalam rangka proses pembangunan masyarakat Jawa yang religiusKata Kunci: hukum Islam; kebudayaan Jawa; profetik.